Baseball fans don't like lumpy batters: Influence of domain knowledge on the access of subordinate meanings. Issue 1 (January 2018) - Wiley, Jennifer; George, Tim; Rayner, Keith
Two experiments investigated the effects of domain knowledge on the resolution of ambiguous words with dominant meanings related to baseball. When placed in a sentence context that strongly biased toward the non-baseball meaning (positive evidence), or excluded the baseball meaning (negative evidence), baseball experts had more difficulty than non-experts resolving the ambiguity. Sentence contexts containing positive evidence supported earlier resolution than did the negative evidence condition for both experts and non-experts. These experiments extend prior findings, and can be seen as support for the reordered access model of lexical access, where both prior knowledge and discourse context influence the availability of word meanings.